KOMUNIKASI TERAPEUTIK KADER DALAM PENYAMPAIAN INFORMASI PROGRAM KELUARGA BERENCANA MKJP DI NAGARI AIE ANGEK - Welda Yulia; Sarmiati Sarmiati (Universitas Negeri Padang, 2020)
The study of therapeutic communication always attracts the attention of the author because there are various points of view of social problems related to aspects of therapeutic communication. Therapeutic communication leads to interpersonal communication. In determining the choice of contraception used by couples of childbearing age, it sometimes depends on the information obtained during counseling. In the family planning program, one of the program achievement indicators is the percentage of using the Long-Term Contraception Method (MKJP). Nagari Aie Angek is one of the villages that has the lowest MKJP achievements in Sijunjung District. Therapeutic communication used in counseling will determine future changes in behavior, including the behavior of choosing MKJP as an option. This study focuses on the therapeutic communication process carried out by cadres in delivering information on the Long-Term Contraception Method (MKJP) in Nagari Aie Angek. The purpose of this study was to determine the therapeutic communication process carried out by cadres in conveying information about MKJP to Fertile Age Couples (PUS). The approach used is a qualitative approach with a case study method. Data collection was carried out through interviews, documentation study, and observation. The results showed that the therapeutic communication carried out by the cadres included verbal messages and media messages. Verbal messages are conveyed from family planning cadres directly to the community, while media messages are distributed by family planning cadres through the installation of pamphlets and posters in public places.